WRITTEN MORNING-GIFT, A SPECIAL LEGAL INSTRUMENT OF MARITAL LAW - Koncz, Ibolya Katalin (European Integration Studies, 2017)
Morning-gift was a term defined in the framework of the legal instruments of marital law. As the instrument of morning-gift was a share in properties rightfully given to a lawfully married wife from the husband’s wealth, the subjects of this instrument were mainly husbands and wives. Written, or contractual morning gift was a particular practice arising from practical reasons and then made part of legal practices by courts. When defining its term, we can accept the standpoint of Knorr, according to whom written morning gift was a contribution of assets promised to be given by one spouse or a third party to the other spouse according to a respective contract, as a consideration for proper marital conduct. As early as in Planum Tabulare, it was stated that “the lawful morning-gift is superseded by written morning-gift, thus the widow cannot claim both, as the provided assets of a man supersedes the provisions of the law”. According to Szladits, the “…husband may undertake contractual obligations with respect to his wife; a written morning-gift annuls the lower-ranked lawful morning-gift”. However, in case the written morning-gift clause is void or ineffective due to any elements of the respective contract, the lawful morning-gift becomes effective again. Consequently, these two kinds of morning-gifts only had the provision not to exist simultaneously, in parallel, therefore could not be effected at the same time.